2021
DOI: 10.1016/j.heliyon.2021.e08446
|View full text |Cite
|
Sign up to set email alerts
|

Articulating the exuberant intricacies of bacterial exopolysaccharides to purge environmental pollutants

Abstract: Microbial exopolysaccharide (EPS) is composed of a mixture of macromolecules such as proteins, polysaccharides, humic-like compounds, and nucleic acids, which encase microbial cells in a three-dimensional matrix. The literature shows that the EPS possess significant properties such as renewable, biodegradable, eco-friendly, non-toxic, and economically valued product, representing it as a green alternative to the synthetic polymer. The cost-effective and green synthesis of the EPS must be encouraged by using ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…Research by Jiang et al [106] found that bacteria exposed to Cr 6+ experience oxidative stress, thereby reducing their bioremediation efficiency. Therefore, bioremediation can be made more effective by applying genetic engineering, developing enzymes that act on the degradation of pollutants [107,108]. That is, microorganisms' resistant to pollutants are the best choice for genetic manipulation [109,110].…”
Section: Recent Knowledge On Biological Remediation Of Soil Water And...mentioning
confidence: 99%
“…Research by Jiang et al [106] found that bacteria exposed to Cr 6+ experience oxidative stress, thereby reducing their bioremediation efficiency. Therefore, bioremediation can be made more effective by applying genetic engineering, developing enzymes that act on the degradation of pollutants [107,108]. That is, microorganisms' resistant to pollutants are the best choice for genetic manipulation [109,110].…”
Section: Recent Knowledge On Biological Remediation Of Soil Water And...mentioning
confidence: 99%
“…Antiviral drugs are also used to control viral infections, however, antiviral drug treatment has its own side effects and are considered expensive. Therefore, scientists are looking for economical and natural ways of treatment with no side effects to humans (Mehta et al 2021; Udayakumar et al 2021). In this regard, polysaccharides of bacterial and algal origins are considered safe for human consumption by the US Food and Drug Administration.…”
Section: Introductionmentioning
confidence: 99%